Strategi Penanggulangan Kemiskinan Pada Komunitas Nelayan Di Lingkungan Bojo, Kelurahan Mallawa, Kecamatan Mallusetasi, Kabupaten Barru - Muhammad Farhansyah R; Muhammad Bibin; Hasrianti Hasrianti (Samakia : Jurnal Ilmu Perikanan, 2025)
This study analyzes the socioeconomic conditions and formulates poverty alleviation strategies for fishermen communities in Bojo Neighborhood, Mallawa Village, Mallusetasi District, Barru Regency. Employing a descriptive-analytic qualitative approach, data were collected through participatory observation, in-depth interviews, focus group discussions, and questionnaires administered to 38 fishing household heads during July–August 2025. Results indicate that most respondents are in the productive age group (31–40 years: 42%), possess elementary education (50%), and earn monthly incomes of IDR 1,000,000–2,500,000 (68%), substantially below the regional minimum wage. Additionally, 87% lack alternative income sources and 95% have never received capital assistance; 97% prioritize modern fishing gear as the most needed support. These findings reflect multidimensional poverty economic, institutional, and human capital which requires integrated interventions. Recommended strategies include strengthening institutions and access to finance, improving infrastructure and fishing technology, enhancing human resource capacity through training, and implementing sustainable marine resource management. Proper application of these measures is expected to increase productivity, income, and economic resilience of coastal fishing communities.